Exploring the future of rural–urban connections in sub-Saharan Africa: modelling urban expansion and its impact on food production in the Addis Ababa region. Issue 2 (3rd July 2017) - Abo-El-Wafa, Hany; Yeshitela, Kumelachew; Pauleit, Stephan
Abstract: The built-up area of Addis Ababa and its surrounding towns is expanding into the peri-urban region leading to high losses of farmland, directly influencing the food production for the urban population. This paper investigates the patterns of settlement growth in the region surrounding Addis Ababa and their impact on peri-urban agriculture using an urban spatial scenario design model. The effects of two population density scenarios are explored within the framework of a proposed master plan. The model output was used to estimate areas of different suitability levels that would be lost to the modelled settlement expansion. The settlement area in 2038 would represent 29% of the case study's total area in the low-density scenario but only 19% in the high-density scenario. Compared to the low-density scenario, the high-density scenario would only require a third of the agricultural land transformed into settlement areas. Settlement development would contribute to higher losses of land suitable for cultivating important export products, high nutritional value and import-substituting products. The scenario approach can support sustainable regional planning for settlement expansion that conserves valuable farmland in the peri-urban area and contributes to building capacity for strategic planning of the city regions of sub-Saharan Africa.